The Children Act and the Oldham League - Dawson, Charles (Statistical and Social Inquiry Society of Ireland, 1912)
The passing of the Children Act, 1908, introduced by the Rt- Hon. Herbert Samuel, M.P., and the establishment of a Children's League in Oldham suggested to me to bring before the Society what the recent law has enacted, and what voluntary effort has effected for the protection and happiness of young children.
Read April 29th, 1910.
Keywords: Child welfare; Oldham Children League; Children Act, 1908; 314.15